Concrete fluidity effects on bond of prestressed tendons for lightweight bridge girders - Perkins, Jake (Kansas State University, 2008)
With limited research being conducted solely on lightweight concrete prestressed bond and current development-length equations based on tests performed on normal-weight members, more investigation on lightweight concrete prestress bond is necessary. Additionally, the effects of water-reducing agents on normal-weight and lightweight concrete need further exploration. The aim of this study was to examine these areas using two locally available lightweight aggregates from Kansas and one from North Carolina to determine if lightweight prestressed concrete bridge girders are a useful alternative for the Kansas Department of Transportation. The lightweight concrete mixes developed were capable of attaining 5000 psi compressive strength in 16 hours and 7000 psi in 28 days. During the large block pull-out test, the average maximum force at pull-out and first observable slip was higher for the block cast with a three inch slump then the companion specimen poured at a nine-inch slump. During flexural testing, the two beams not reaching nominal moment capacity, KC-9 and STA-9, failed in compression without strand end slip. The moment capacity was considerably greater for three-inch slump members than the companion specimen placed with nine-inch slump concrete.
Keywords: Lightweight concrete; Prestressed; Fluidity; Bridge Girders; Development Length; Transfer Length; Engineering, Civil (0543); Engineering, Materials Science (0794)